2011
DOI: 10.1002/cbf.1742
|View full text |Cite
|
Sign up to set email alerts
|

The 8‐oxoguanine DNA N‐glycosylase 1 (hOGG1) Ser326Cys variant affects the susceptibility to Graves' disease

Abstract: Oxidative DNA damage, caused by either endogenous or exogenous sources of reactive oxygen species (ROS), has been linked several diseases including Graves' disease (GD). 7,8-Dihydro-8-oxoguanine (8-oxoG) is a major lesion produced by ROS and is considered a key biomarker of oxidative DNA damage. In humans, 8-oxoG is mainly repaired by 8-oxoguanine DNA N-glycosylase-1 (hOGG1), which is an essential component of the base excision repair (BER) pathway. The functional studies showed that hOGG1 Ser326Cys polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
0
15
2
Order By: Relevance
“…Tanrikulu et al assessed hOGG1 Ser326Cys polymorphism (rs1052133) as a candidate risk factor for GD. They found that Cys/Cys genotype had a 3.5-fold (95% CI: 2.10–6.01, P < 0.001) and the Cys allele had 1.83-fold (95% CI: 1.43–2.34, P < 0.001) increase in the risk for developing Grave's disease in their population [46]. The Ser326Cys polymorphism in hOGG1 gene was shown to reduce the hOGG1 activity in both in vitro and in vivo studies [46].…”
Section: Oxidative Stress In Graves' Disease and Retroorbital Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanrikulu et al assessed hOGG1 Ser326Cys polymorphism (rs1052133) as a candidate risk factor for GD. They found that Cys/Cys genotype had a 3.5-fold (95% CI: 2.10–6.01, P < 0.001) and the Cys allele had 1.83-fold (95% CI: 1.43–2.34, P < 0.001) increase in the risk for developing Grave's disease in their population [46]. The Ser326Cys polymorphism in hOGG1 gene was shown to reduce the hOGG1 activity in both in vitro and in vivo studies [46].…”
Section: Oxidative Stress In Graves' Disease and Retroorbital Tissuesmentioning
confidence: 99%
“…They found that Cys/Cys genotype had a 3.5-fold (95% CI: 2.10–6.01, P < 0.001) and the Cys allele had 1.83-fold (95% CI: 1.43–2.34, P < 0.001) increase in the risk for developing Grave's disease in their population [46]. The Ser326Cys polymorphism in hOGG1 gene was shown to reduce the hOGG1 activity in both in vitro and in vivo studies [46]. As the production of 8-oxoG is increased both in retroorbital fibroblasts and in urine of patients with GD and correlates with the disease activity, it could be argued that reduced hOGG1 activity causes increased DNA damage and increased OS making subject more susceptible to development of Graves' orbitopathy [43, 44].…”
Section: Oxidative Stress In Graves' Disease and Retroorbital Tissuesmentioning
confidence: 99%
“…Considering the DNA repair efficiency, homozygous hOGG1 1245 CC genotype has the highest DNA repair activity followed by the heterozygous hOGG1 1245 CG genotype and then the homozygous hOGG1 1245 GG genotype in order [ 9 ]. This discrepancy in hOGG1 repair activity implies that hOGG1 1245 GG genotype with lower efficiency in DNA repair might be related to a higher level of 8-OHdG in human tissues [ 10 ], and may contribute to the development of several human degenerative diseases, including type 2 diabetes mellitus [ 11 ], Huntington’s disease [ 12 ], chronic obstructive pulmonary disease [ 13 ], Graves’ ophthalmopathy [ 14 ], and higher susceptibility to cancer formation, including lung cancer [ 15 ] and esophageal squamous cell carcinoma [ 16 ]. However, the role of hOGG1 C1245G polymorphism in the pathogenesis of SLE has remained obscure.…”
Section: Introductionmentioning
confidence: 99%
“…The role of accumula on of oxida ve DNA damage, however, was unequivocally confirmed, specifically for Grave's ophtalmopathy [131]. The homozygous Cys/Cys genotype of the Ser326Cys polymorphism in the hOGG1 gene was found to be associated with nearly 4-fold increase in the risk for developing Graves' disease [132].…”
Section: Neil Genesmentioning
confidence: 98%